Implementation of Organizational Culture in Islamic Da'wah Management to Increase Community Participation in Lau Dendang, Deli Serdang - Elvira Nurlita Sibaran; Muhammad Zaid; Mei Zhura Afnidar (Journal of Global Islamic Economic Studies, 2024)
This study aims to describe the implementation of organizational culture in the management of da'wah that can enhance community participation in Lau Dendang Village, Percut Sei Tuan District, Deli Serdang Regency. Using a qualitative approach with a descriptive design, data was collected through interviews and direct observations of various parties involved in da'wah activities, including mosque administrators, community leaders, and community members. Data analysis was conducted by identifying patterns and relevant themes from the narrative information and official documents obtained. The results of the study indicate that the applied organizational culture, such as values of togetherness and collaboration, plays a crucial role in improving community participation. This culture fosters a sense of ownership of the da'wah programs and strengthens social solidarity. However, there are also challenges faced, such as a lack of awareness and active participation from some community members, as well as resource limitations. These findings are expected to provide insights for da'wah managers and the community to optimize participation in da'wah activities in the village.